STROKE - REASON, TREATMENT (Proceedings of International Educators Conference, 2024)
Stroke (lat. strokeus - "attack, blow") is an acute disorder of blood circulation in the brain, which is characterized by the appearance of focal or general neurological symptoms. The disease ranks third in terms of mortality after cardiovascular and oncological diseases. About 2/3 of stroke cases occur in elderly people (after 60 years). A stroke is an acute disorder of cerebral blood circulation, which is characterized by the appearance of focal or general neurological symptoms.